Signs of Coloniality in Brazilian Communicational Approaches: the first quadrennium of the papers from the proceedings of Compós (2000-2003) (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article investigates the extent to which signs of modern European and North American coloniality are present in the field of Communication in Brazil. It considers that there is coloniality of Latin American knowledge, delimited in Brazilian communicational approaches, elaborated and systematized in the papers from the proceedings of the first Compós quadrennium (2000-2003), a period not studied in other papers. The event is one of the main events in the country. The investigation considers, above all, the nationality category, as well as the authors’ genders and their skin color, which reverberate such coloniality. The analysis of the manually collected data was carried out using R programming language and paid attention to the most cited works and authors for each category. The results show the prevalence of European and North American white male authors in such references.
Keywords: Latin America; Coloniality; Compós; Epistemology of Communication; Communication Theory